Bioactive of betel leaves extract grown in Vinh Long province and its application to extend shelf-life of Da Xanh pomelo - Tran, Thanh Truc; Phan, Minh Trong; To Nguyen, Phuoc Mai; Nguyen, Van Muoi (Vietnam Journal of Science and Technology, 2025)
It is well known that plant extract is a safe additive for coating systems that can extend fruit shelf-life. In this study, bioactive compounds of betel leaves (Piper betle L.) grown in Vinh Long province were extracted, characterized, and proposed to use in the coating preparation for Da Xanh pomelo (Citrus maxima (Burn.) Merr.). Characteristic tests showed that piper betel leaves extract (PBE) had high phenolic content and antioxidant activities. It could also inhibit seven different strains of mould presented in Da Xanh peel. Thus, PBE proved to be a suitable additive to coating Da Xanh pomelo. PBE was then mixed in the coating preparation at different concentrations (150; 200; 250; 300, and 400 µg GAE/mL), and the fruits were then coated with the coating sample. After 15 days of storage, Da Xanh pomelo coated at 250 µg GAE/mL showed the least changes in ∆E value, weight loss, and total yeast and mould count. Extended storage test results also showed that Da Xanh pomelos coated with betel leaf extract-added preparation were stable after 30 days of storage at room condition.